Genetic and Functional Characterization of a Conjugative KpVP-2-Type Virulence Plasmid From a Clinical Klebsiella pneumoniae Strain - Yang, Xuemei; Liu, Xiaoxuan; Xu, Yating; Yang, Chen; Chan, Edward Wai-Chi; Shum, Hoi-ping; Chen, Sheng (Frontiers in Microbiology, 2022)
The main mechanisms of virulence in Klebsiella pneumoniae are the acquisition of K. pneumoniae virulence plasmids (KpVPs), which include two dominant types, KpVP1 (carrying iuc1, iro1, rmpA and rmpA2) and KpVP2 (carrying iuc2, iro2 and rmpA). Both are nonconjugative and associated with different hypervirulent clones. In contrast to KpVP1 that was reported in K1, K2 and other serotypes of K. pneumoniae, KpVP2 was only reported in K2 strains and rarely characterized. In this study, we identified a conjugative KpVP-2 type virulence plasmid for the first time from a clinical hypervirulent K. pneumoniae strain. This plasmid was generated by integration of conjugative transfer genes into the KpVP-2 type plasmid Kp52.145 II and could be readily conjugated to Escherichia coli strain EC600 and K. pneumoniae strains of various types which are clinically existing, mediating hypervirulence. Furthermore, this kind of conjugative KpVP2 type virulence plasmid has been disseminated in clinical settings in Hong Kong and other regions of the world. Generation of conjugative virulence plasmid may promote its transmission and explain the evolution of this type of virulence plasmid.